ENGLISH-INDONESIAN TRANSLATION EQUIVALENCE OF VERBS FOUND IN DESPICABLE ME MOVIE - Swari Fadhillah and Lidiman Sahat Martua Sinaga (LINGUISTICA, 2015)
This research focused on translation equivalence of verbs found in Despicable MeMovie. The research was conducted by using qualitative method. The source ofdata was collected from the movie script and its translation in Indonesian, and thedata was limited on the verbs.The objective of the study are to find out the type oftranslation equivalence in Despicable Me Movie script and its translation, themost dominant type of equivalence found in the movie script and its translation,and the naturalness of expression in the translation of movie script. The data wasanalyzed based on Nida (McGuire, 1991) theory about translation equivalence.There are two types of equivalences, they are: (1) Formal Equivalence, whichfocus attention on the message itself, in both form and content, and (2) D-Etranslation, which is based upon the principle of equivalence effect.